On Studying the Hierarchical Inter-Relationships amongst Challenges to Using Info-Graphics, implementation of Ideation Tools and Techniques, as well as Usage of Video Technologies in Education - Arnav Jain; Remica Aggarwal (Recent Research Advances in Arts and Social Studies Vol. 9, 2024)
Info-graphics are a great way to help people process information in a way that’s most appealing, comfortable and accessible to them. This includes providing words, images, and even interactive elements to help with attention, memory, and recall processes. Ideation is an essential part of the design process, both in education and practice and a crucial part of the Design Thinking process. Design Thinking is all about breaking down barriers and removing the obstacles that typically block innovation. This paper deals with three parts focusing on challenges to using info-graphics, challenges to implementation of ideation tools and challenges to use of video technologies in education respectively. Further, the hierarchical inter-relationships amongst the challenges have been studied using VAXO technique-based matrices.